Developing Qaf Online System for Quranic contests - Abdo Khaled, Nashwan; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Al-Aghbari, Mohammed; Chamie, Marhaf; Zaid, Mohammed; ,; , (2018)
Nowadays, the use of IT is playing a crucial rule in almost all aspects of life. This paper will highlight the importance of using IT in Quranic education. With that, it is observed that many Quranic institutions are using IT in their daily work, but there is still a lack in integrating IT systems into some Quranic programs that require utilizing IT for better efficiency. Qaf system has been proposed and developed to realize this objective for the whole processes of Quranic contests, which is built upon an experience of 10 years in conducting Quranic contests. The system encompasses 5 main modules – User Management Module, Applications Module, Seasons & Sessions Module, Questions & Evaluations Module, and Result Module. For smooth operation of the system, it has been tested with 700 users. With the use of this system in Quranic contests, efficiency and effectiveness are attained in terms of time, flow of processes, and effort.